2020
DOI: 10.37160/jikg.v1i3.543
|View full text |Cite
|
Sign up to set email alerts
|

Erupsi Gigi Molar Pertama Permanen Berdasarkan Letak Geografis Pesisir Pantai dan Pegunungan di Kabupaten Pacitan

Abstract: Masalah dalam penelitian ini yaitu ketidaksesuaian kecepatan erupsi gigi di wilayah pesisir pantai dan pegunungan. Tujuan Penelitian ini adalah untuk mengetahui perbedaan erupsi gigi molar pertama permanen rahang atas dan bawah berdasarkan letak geografis pesisir pantai dan pegunungan Kabupaten Pacitan. Jenis penelitian yang digunakan adalah penelitian observasional analitik dengan pendekatan cross sectional. Sasaran dalam penelitian ini adalah sebagian siswa pada SD di daerah pesisir pantai yaitu Kecamatan Ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…[18] Fish meat consumed by the Puger population is rich in macronutrients and micronutrients essential for humans, including protein, calcium, phosphorus, iron, magnesium, iodine, zinc, vitamin D, and other minerals essential for tooth growth and development. [19] This is in accordance with research conducted by Koenela et al [10] , who found that dental eruption tends to occur earlier in coastal areas compared to mountain regions, mainly due to the high consumption of fish by coastal people.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[18] Fish meat consumed by the Puger population is rich in macronutrients and micronutrients essential for humans, including protein, calcium, phosphorus, iron, magnesium, iodine, zinc, vitamin D, and other minerals essential for tooth growth and development. [19] This is in accordance with research conducted by Koenela et al [10] , who found that dental eruption tends to occur earlier in coastal areas compared to mountain regions, mainly due to the high consumption of fish by coastal people.…”
Section: Discussionsupporting
confidence: 90%
“…The observations were categorized into four phases as follows: 0.00 = tooth not erupted, 0.25 = cusp erupted until quarter of the height of the tooth is erupted, 0.50 = half of the height of the tooth is erupted, 1.00 = tooth has more than half until the whole clinical crown erupted. [10] Ethicalconsiderations Written, informedconsentwas obtainedfrom each studyparticipant. Participants were informed about the objectivesof the study and the confidential and non-binding nature ofparticipationinthestudy.Ethical approval for this study (No.1863/UN25.8/KEPK/DL/2023) was provided by the Ethical Committee of Medical Research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation